Towards a political economy framework for wind power: Does China break the mould? - Michael R. Davidson; Frederich Kahrl; Valerie J. Karplus (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We propose a general taxonomy of the political economy challenges to wind power development and integration, highlighting the implications in terms of actors, interests, and risks. Applying this framework to three functions in China's electricity sector - planning and project approval, generator cost recovery, and balancing area coordination - we find evidence of challenges common across countries with significant wind investments, despite institutional and industry characteristics that are unique to China. We argue that resolving these political economy challenges is as important to facilitating the role of wind and other renewable energies in a low carbon energy transition as providing dedicated technical and policy support. China is no exception.
Keywords: Q42; P16; L51; 330; wind power; energy policy; political economy; electricity regulation; China